Acute Stroke Care in the With-COVID-19 Era: Experience at a Comprehensive Stroke Center in Japan - Koge, Junpei; Shiozawa, Masayuki; Toyoda, Kazunori (Frontiers in Neurology, 2021)
Introduction: The pandemic of coronavirus disease 2019 (COVID-19) has had a significant impact on stroke healthcare, including the prehospital care system and in-hospital workflow. Japan experienced the outbreak of COVID-19 and the State of Emergency was declared during April 2020 and May 2020. The aim of the present study was to clarify the effect of the COVID-19 pandemic on a comprehensive stroke center in Japan. Methods: We retrospectively reviewed consecutive patients with acute ischemic stroke admitted in our institute between December 2019 and July 2020. The patients who underwent reperfusion therapy (intravenous thrombolysis and/or mechanical thrombectomy) were divided into the pre-COVID-19 period (December 2019 to March 2020) and the With-COVID-19 period (April 2020 to July 2020). Study outcomes were the number of stroke admissions in our institute, workflow time metrics, the-frequency of modified Rankin Scale score 0-2 at discharge and brain imaging modalities before reperfusion therapy in patients who underwent reperfusion therapy. Results: In our institute, the number of stroke admissions decreased during the State of Emergency and then increased after the lifting of the State of Emergency. Amongst patients who underwent reperfusion therapy (median age, 77 years; female 27%; median baseline National Institutes of Health Stroke Scale score, 10), times from hospital arrival to imaging (25 [21–33] minutes versus 30 [25–38] minutes, P=0.03) and to thrombolysis (38 [31–52] minutes versus 51 [37–64] minutes P=0.03) were prolonged compared with the pre-COVID-19 period. There was no significant difference in the frequency of modified Rankin Scale score 0-2 at discharge between the two periods (32 % versus 45 %, P=0.21). The proportion of computed tomography versus magnetic resonance imaging as an emergency brain imaging tool before reperfusion therapy changed, with computed tomography having become predominant in the With-COVID-19 period. Conclusions: In our institute, the number of stroke admissions, workflow time metrics and imaging modalities for reperfusion therapy were affected by COVID-19 pandemic.